2019
DOI: 10.1371/journal.pone.0214819
|View full text |Cite
|
Sign up to set email alerts
|

The sound of speed: How grunting affects opponents’ anticipation in tennis

Abstract: Grunting in tennis is a widespread phenomenon and whether it influences opponents’ predictions of ball trajectory—and if so, why—is subject of ongoing debate. Two alternative hypotheses have been proposed to explain why grunting may impede opponents’ predictions, referred to as the distraction account (i.e., grunts capture attentional resources necessary for anticipation) and the multisensory integration account (i.e., auditory information from the grunt systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…In sum, the behavioral results highlight the performance determining role of ecological auditory information for reaction speed in sport-specific multisensory environments. It supports previous behavioral research in sport science emphasizing the importance of ecological auditory information especially in racquet sports such as table tennis and tennis ( Müller et al, 2019 ; Klein-Soetebier et al, 2020 ). The auditory system may thus be a relevant target for sport-specific training approaches which is in line with previous research on the positive effects of acoustic reafference training to improve motor performance ( Pizzera et al, 2017 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In sum, the behavioral results highlight the performance determining role of ecological auditory information for reaction speed in sport-specific multisensory environments. It supports previous behavioral research in sport science emphasizing the importance of ecological auditory information especially in racquet sports such as table tennis and tennis ( Müller et al, 2019 ; Klein-Soetebier et al, 2020 ). The auditory system may thus be a relevant target for sport-specific training approaches which is in line with previous research on the positive effects of acoustic reafference training to improve motor performance ( Pizzera et al, 2017 ).…”
Section: Discussionsupporting
confidence: 87%
“…Performing sport-specific motor tasks in auditory deprived conditions resulted in lower precision performance in table tennis ( Klein-Soetebier et al, 2020 ) and a higher rate of lost matches in tennis ( Takeuchi, 1993 ). Similarly, masking natural auditory cues in tennis by grunting sounds systematically affected the anticipated ball trajectory dependent on grunt intensity ( Müller et al, 2019 ) while a manipulation of audio-visual stimulus congruency and sound intensity delays the response time and anticipated length of volleyball serves and tennis strokes, respectively ( Cañal-Bruland et al, 2018 ; Sors et al, 2018a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of studies in the last few years further corroborated the relevance of auditory information in anticipating opponents' actions, not only in tennis (Cañal-Bruland, Müller, Lach, & Spence, 2018;Müller, Jauernig, & Cañal-Bruland, 2019), but also in other sports. Particularly, Camponogara, Rodger, Craig, and Cesari (2017) highlighted that basketball players are able to anticipate the action as well as intentions of an attacker from the sound he produces while moving toward them.…”
Section: The Relevance Of Auditory Information In Sportmentioning
confidence: 87%
“…Previous studies in tennis have suggested that grunting may effect an opponent's anticipatory judgment of a shot's trajectory due to distractive effects or mechanisms of multisensory integration. 42,43 As a result, grunting may provide the baseball pitcher an advantage of, not only enhanced throwing velocity, but also impairment of the batter's ability to perceive pitch trajectory. In our study, we utilized a sample of collegiate-level pitchers.…”
Section: Discussionmentioning
confidence: 99%